The Development of Children’s Psychology in the Orang Rimba Community: A Cultural Psychological Analysis in Kedundung Muda – Jambi - Ditta Febrieta; Ajat Sudrajat (Jurnal Ilmiah Global Education, 2026)
Children’s psychosocial development is inseparable from the cultural and ecological environments that structure their daily lives. This study investigates the psychosocial development of Orang Rimba children in the Kedundung Muda community of Jambi through a cultural psychology framework, arguing that culturally embedded practices remain central to understanding developmental trajectories in Indigenous contexts. Employing a descriptive qualitative design, the study integrates a literature review with secondary ethnographic analysis of caregiving norms, social organization, and cultural interaction within Orang Rimba society. The findings demonstrate that children’s psychosocial development is shaped not only by customary values, kinship relations, and ecological engagements but also by the community’s adaptive strategies in negotiating external pressures such as state policies, formal schooling, and forest ecological change. These pressures generate identity tensions, role ambiguities, and shifts in caregiving practices, revealing the fragility and resilience of Indigenous developmental systems under structural transformation. The study contends that culturally informed frameworks are indispensable for designing educational and social interventions that respect and sustain Indigenous lifeworlds.